2016
DOI: 10.1111/tpj.13188
|View full text |Cite
|
Sign up to set email alerts
|

Auxin‐mediated lamina growth in tomato leaves is restricted by two parallel mechanisms

Abstract: SUMMARYIn the development of tomato compound leaves, local auxin maxima points, separated by the expression of the Aux/IAA protein SlIAA9/ENTIRE (E), direct the formation of discrete leaflets along the leaf margin. The local auxin maxima promote leaflet initiation, while E acts between leaflets to inhibit auxin response and lamina growth, enabling leaflet separation. Here, we show that a group of auxin response factors (ARFs), which are targeted by miR160, antagonizes auxin response and lamina growth in conjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 86 publications
1
58
0
Order By: Relevance
“…Class C ARFs also promote the formation of shoot meristems in undifferentiated callus by directly repressing negative regulators of cytokinin signalling (Qiao et al ., ; Liu et al ., ). Auxin response reporters have been shown to be both induced and repressed by class C ARF activity in angiosperms, suggesting a contextual role for these genes in development (Mallory et al ., ; Wang et al ., ; Liu et al ., ; Ben‐Gera et al ., ). Irrespective of their function as transcriptional repressors or activators, genetic studies suggest that class C ARFs have the potential to antagonize auxin signalling (Turner et al ., ; Ben‐Gera et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Class C ARFs also promote the formation of shoot meristems in undifferentiated callus by directly repressing negative regulators of cytokinin signalling (Qiao et al ., ; Liu et al ., ). Auxin response reporters have been shown to be both induced and repressed by class C ARF activity in angiosperms, suggesting a contextual role for these genes in development (Mallory et al ., ; Wang et al ., ; Liu et al ., ; Ben‐Gera et al ., ). Irrespective of their function as transcriptional repressors or activators, genetic studies suggest that class C ARFs have the potential to antagonize auxin signalling (Turner et al ., ; Ben‐Gera et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The class C ARF/MIR160 module in angiosperms regulates a range of processes including leaf margin complexity and lamina growth (Mallory et al ., ; Hendelman et al ., ; Ben‐Gera et al ., ), nodule formation in soybean roots (Turner et al ., ; Nizampatnam et al ., ), root meristem patterning (Wang et al ., ; Ding & Friml, ; Bennett et al ., ) floral determinacy (Liu et al ., ), ovary and fruit patterning, floral organ abscission (Damodharan et al ., ) and seed germination (Liu et al ., , ). Class C ARFs also promote the formation of shoot meristems in undifferentiated callus by directly repressing negative regulators of cytokinin signalling (Qiao et al ., ; Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fine regulation of ARF17 expression by miR160 was suggested to play a role in Arabidopsis tapetum development and pollen wall formation (Wang et al ., ). In situ hybridizations indicated that the expression domains of sly‐miR160 and SlARF10A overlap at the margins of the leaf and leaflet primordia (Hendelman et al ., ; Ben‐Gera et al ., ). In addition, our data demonstrate the high sensitivity of SlARF10A expression to even small changes in sly‐miR160a levels (Figure b).…”
Section: Discussionmentioning
confidence: 97%
“…SlARF10A has been proposed to function as an auxin‐response inhibitor according to a protoplast assay (Zouine et al ., ). Consistent with this finding, SlARF10A was suggested to be involved in the spatial restriction of the auxin response that drive leaf blade outgrowth (Ben‐Gera et al ., ). Therefore, we concluded that by fine tuning the expression of this repressor ARF, sly‐miR160a promoted auxin‐dependent compound leaf initiation, primary and secondary morphogenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation